ASSESSING CABERGOLINE RESPONSIVENESS AMONG PATIENTS WITH PITUITARY PROLACTINOMA IN NORTH IRAQ - Ahmed, Mazyar Jabbar (Journal of Sulaimani Medical College, 2024)
Background Prolactinoma accounts for roughly half of all pituitary tumours. Dopamine agonists are preferred for the treatment of prolactinomas. Objectives This study aimed to determine the response rate to both biochemical and anatomical decreases in prolactinoma levels. Methods This current study was designed before and after a clinical trial (quasi-experimental study). All cases consulted the Endocrinology Unit of Razen Private Clinic, Erbil Teaching Hospital, and PAR Private Hospitals for hyperprolactinemia underwent thorough hormonal and imaging evaluations. Among them, only prolactinoma cases were selected for the study, which was performed over a one-year duration. Cabergoline tablet was given in two different oral regimens, 0.5mg/ week or 1 mg/week, in two divided doses according to clinical evaluation and prolactin hormone level. Results Sixty four patients diagnosed with prolactinoma enrolled in the current study. Patients with microadenoma type responded better to cabergoline therapy than macroadenoma patients. There was no signifi cant association between sex and cabergoline dose and clinical presentation (p–values ˃ 0.05). The statistically signifi cant difference in prolactin and tumour size by MRI was observed before and after treatment (p: <0.001). Conclusion This study obtained excellent effectiveness and tolerance of cabergoline in the treatment of pathological hyperprolactinemia. It also demonstrated that very few patients experienced side effects that were intolerable or insuffi cient clinical response. Patients with hyperprolactinemia due to microprolactinoma got more benefi t from treatment by cabergoline than those with macroprolactinoma.
Keywords: Cabergoline; Iraq; Pituitary gland; Prolactinoma